Managing the Impact of Speculative Risk Activities in Mining Communities in Ghana - Buertey , Joseph Teye I.; Atsrim , Felix K.; Boateng , Kwasi; Doe, David; Asirifi , Ransford (An Overview on Business, Management and Economics Research Vol. 5, 2023)
Ghana's mining industry's compensation and resettlement laws prohibit speculative development as a risk protection for mining companies. Despite the law, mining communities desire to profit from their speculation. This chapter examines the effect of speculative mining activities and issues of compensation on both the speculators and the mining companies within some mining communities in Ghana. As a qualitative-based research, data was collected purposively using questionnaires, observation, and focus group discussions from 93 people living within communities associated with speculative mining activities. Univariate statistics were used to analyse the data for further descriptive discussion of the key findings. The study revealed that the community folks learned about potential speculative areas through preliminary reconnaissance and preparatory activities of the companies in these areas. The research established that whereas the mining companies were negatively impacted by speculative activities because of increased budgets, community agitations, delays in the commencement of mining activities and threats to resettlement officers' lives during fieldwork; the community folks were also affected by delays in resettlement compensation processing and sometimes losses due to denial in payment. Again, at a 5% significance level, it was established that speculation threatens the sustainability of the mining business because of the plurality of speculative economic activities in the region of operation of mining companies. Even though it is envisaged that speculative mining activities will continue, it has been proposed that to reduce speculative activities in mining communities, there must be increased awareness through civic education to the effect that legally, mining companies are not expected to pay pre-moratorium for speculative economic activities. This may go a long way to improve the relationship between the communities and the mining companies.